JENIS-JENIS TUMBUHAN SEBAGAI SUMBER PAKAN JALAK BALI (Leucopsar rothschildi S.) DI DESA PED, NUSA PENIDA, KLUNGKUNG, BALI - I Ketut Ginantra; A.A.G. Raka Dalem; Sang Ketut Sudirga; I.G.N. Bayu Wirayudha (Bumi Lestari Journal of Environment, 2009)
A study on plants species as resource of food for Bali Starling (Leucopsar rothschildi Stresemann, 1912) was carried out in Ped Village, Nusa Penida, Klungkung Bali, Indonesia between March-April and between August-September, 2006. Explorations methods were conducted in making inventory of plants species and part of plants as food resource. Direct observations were conducted to observe feeding activity of the starling after release. Results of this study showed that 105 plants species have been identified in Ped village. About 30 species (in varied habitus of trees, shrubs, and herbs) acted as food resources for the starling. Part of plants species which had been used as food resources were fruits and seeds. Besides plants as food sources, insects were also available on the studi site (such as grasshopper, ants, caterpillars, butterflies). In addition there were also small reptiles as source of food for the the bird. Plants availability as source of food supports ex-situ conservations of Bali Starling in Ped village.